In vivo Wound Healing Activity of Tamanu Oil (Calophyllum inophyllum l.) Extracted by Cold-Pressed and Hot-Pressed Methods and Their Fatty Acids Composition - Rakhmawati, Rita; Wahyuni, Dinar Sari Cahyaningrum; Ainurofiq, Ahmad; Hadi, Saptono; Choiri, Syaiful; Retnaningtyas, Estu; Pratama, Tiara Dewi Salindri (Majalah Obat Tradisional, 2024)
Tamanu oil is a promising natural wound healer due to its chemical compounds, particularly fatty acids. Cold-pressed or hot-pressed methods are commonly used to obtain this oil from Calophyllum seed. However, there needs to be research documenting the impact of these two extraction methods on the fatty acid profile and wound healing activity. Therefore, the study aims to characterize the fatty acid profiles of cold-pressed and hot-pressed tamanu oils using Gas Chromatography and evaluate their wound healing activity in vivo. The fatty acid profiles were analyzed using GC, and the wound healing tests were conducted on animal subjects divided into four groups: negative control, positive control (Bioplacenton®), cold-pressed tamanu oil, and hot-pressed tamanu oil. Cold-pressed tamanu oil showed superior fatty acid characteristics with an acid value of 38,71 Mg KOH/g fat and a peroxide value of 3,0095 mEq O2/kg, indicating that oil is stable against oxidation.  The length of the wound was observed daily for up to 8 days to assess its effect. The parameters observed were the percentage of wound healing and the total AUC based on the average length of the wound. Cold-pressed tamanu oil demonstrated the highest wound healing efficacy compared to both the positive control and hot-pressed tamanu oils. Both cold (11,67± 0,78) and hot-pressed tamanu oil (11,87 ± 0,61) exhibited significant differences in AUC value compared to the negative control group (13,07 ± 0,38), highlighting the potential of tamanu oil as a wound healing agent.